2021
DOI: 10.1111/1756-185x.14050
|View full text |Cite
|
Sign up to set email alerts
|

The readiness of pediatric rheumatology patients and their parents to transition to adult‐oriented treatment

Abstract: Introduction Transition is a planned process of pediatric patients from child‐centered to adult‐oriented treatment. Transitional care for patients with chronic diseases is essential. The present study aimed to evaluate the readiness of patients with rheumatic diseases and their parents for transition process. Method This is a cross‐sectional, single‐center study. All patients and their parents were questioned about their awareness of and willingness to undergo transitional care. Transition Readiness Assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
0
10
1
Order By: Relevance
“…Similar to our results, the other authors found no significant difference in total TRAQ scores between female and male JIA patients. 4,29,30 In contrast to our findings, Bingam et al 6 reported that having a concomitant disease, family member with autoimmune disease, and longer disease duration was associated with higher self-reported independence and transition readiness. We found no significant association between disease activity or number of previous hospitalizations and readiness for transition.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Similar to our results, the other authors found no significant difference in total TRAQ scores between female and male JIA patients. 4,29,30 In contrast to our findings, Bingam et al 6 reported that having a concomitant disease, family member with autoimmune disease, and longer disease duration was associated with higher self-reported independence and transition readiness. We found no significant association between disease activity or number of previous hospitalizations and readiness for transition.…”
Section: Discussioncontrasting
confidence: 99%
“…This might be explained by the fact that parents of children with chronic diseases are overprotective in caring for their children. Sönmez et al 30 also reported similar results.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…A commonly used patient-reported outcome measure (PROM) during transition is the Transition Readiness Assessment Questionnaire (TRAQ-20), a generic questionnaire (3,(11)(12)(13)(14)(15)(16)(17)(18). TRAQ has good internal reliability and has been validated in adolescents and young adults (AYAs) with various chronic diseases (19), but not in IBD.…”
mentioning
confidence: 99%